Genome-wide pathway analysis for diabetic nephropathy in type 1 diabetes. (2nd January 2016) - Lee, Young Ho; Song, Gwan Gyu
Abstract: Objective : The aim of this study was to identify candidate single-nucleotide polymorphisms (SNPs) that might play a role in susceptibility to diabetic nephropathy (DN) in type 1 diabetes, elucidate their potential mechanisms, and generate SNP-to-gene-to-pathway hypotheses. Methods : A genome-wide association study (GWAS) dataset of DN in type 1 diabetes, which included 345, 363 SNPs from a total of 1, 705 samples (820 DN cases and 885 normoalbuminuric controls) of European ancestry, was used in this study. The Identify Candidate Causal SNPs and Pathways (ICSNPathway) analysis was applied to the GWAS dataset. Results : ICSNPathway analysis identified 14 candidate SNPs, 10 genes, and 19 pathways, which in turn revealed 10 hypothetical biological mechanisms. The strongest hypothetical biological mechanism was one in which rs4740 altered the role of EBI3 in various pathways and processes, including regulation of the cytokine biosynthetic process, cytokine metabolic process, positive regulation of the cytokine biosynthetic process, regulation of the interferon gamma biosynthetic process, and interferon gamma production (0.008 ≤ p < 0.001; 0.047 ≤ false discovery rate [FDR] ≤ 0.002). This next most strongly supported hypothesis was the modulation of NMUR2 by rs982715, rs4958531, 4958532, rs1895245, and rs4958535 to affect its role in various pathways and processes, including calcium-mediated signaling and peptide receptor activity, and G-protein activity ( p < 0.001, 0.002; FDR = 0.005, 0.049, respectively). Conclusions : By using the ICSNPathway to analyze the DN GWAS data, we identified 14 candidate SNPs, 10 genes (including EBI3, NMUR2, and EFNA1 ), and 19 pathways that likely contribute to the susceptibility to DN in type 1 diabetes.